New Medical Schools in Africa: Challenges and Opportunities. CONSAMS and Value of Working in Consortia - Quentin Eichbaum; Marius Hedimbi; Kasonde Bowa; Celso Belo; Olli Vainio; Johnstone Kumwenda; Peter Nyarango (Ubiquity Press, 2015)
CONSAMS; consortia; new African medical schools; admissions; accreditation; research; interdependence